Non-contiguous finished genome sequence and description of Clostridium dakarense sp. nov. Issue 1 (July 2013) - Lo, Cheikh; Mishra, Ajay; Padhmanabhan, Roshan; Samb Ba, Bissoume; Sow, Amy; Robert, Catherine; Couderc, Carine; Faye, Ngor; Raoult, Didier; Fournier, Pierre-Edouard; Fenollar, Florence
Abstract Clostridium dakarense strain FF1T, is the type strain ofClostridium dakarense sp. nov., a new species within the genusClostridium . This strain, whose genome is described here, was isolated from the fecal flora of a 4-month-old Senegalese child suffering from gastroenteritis.C. dakarense sp. nov. strain FF1T is an obligate anaerobic Gram-positive bacillus. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 3, 735, 762 bp long genome (1 chromosome but no plasmid) exhibits a G+C content of 27.98% and contains 3, 843 protein-coding and 73 RNA genes, including 8 rRNA genes.